PENGARUH PENGGUNAAN MEDIA VIDEO TUTORIAL DAN MOTIVASI TERHADAP HASIL BELAJAR DASAR-DASAR SENI RUPA - RAHAYU GUSWIRA NINGSIH, Dr. Ramalis Hakim, M.Pd. (Universitas Negeri Padang, 2019)
The reseacrh puposed to find out the effect of using video tutorial media and motivation on the results of learning the basics of art to class X of students at SMKN 4 Padang. This type of the research is quantitative using quasi-experimental methods. In its implementation, this study was initiated first with a learning motivaton test by giving a questionnaire then post-test in the form of an action test / practice. The data was obtained by collecting learning outcomes tests. The results of this study indicated of : students who were taught using video tutorial media, their learning outcomes of students who were taught using convensional / ordinary media. That means that the used of video tutorial media in learning is very well used by every educator, because it can improved student learning outcomes. As in the subjects of the basics of art at SMK N. 4 Padang.Keywords : Video tutorial media, motivation, learning outcomes